Comparison of bacterial culture and 16S rRNA community profiling by clonal analysis and pyrosequencing for the characterization of the dentine caries-associated microbiome - Schulze-Schweifing, Kathrin; Banerjee, Avijit; Wade, William G. (Frontiers in Cellular and Infection Microbiology, 2014)
Culture-independent analyses have greatly expanded knowledge regarding the composition of complex bacterial communities including those associated with oral diseases. A consistent finding from such studies, however, has been the under-reporting of members of the phylum Actinobacteria. In this study, five pairs of broad range primers targeting 16S rRNA genes were used in clonal analysis of 6 samples collected from tooth lesions involving dentine in subjects with active caries. Samples were also subjected to cultural analysis and pyrosequencing by means of the 454 platform. A diverse bacterial community of 229 species-level taxa was revealed by culture and clonal analysis, dominated by representatives of the genera Prevotella, Lactobacillus, Selenomonas and Streptococcus. The five most abundant species were: Lactobacillus gasseri, Prevotella denticola, Alloprevotella tannerae, S. mutans and Streptococcus sp. HOT 070, which together made up 31.6 % of the sequences. Two samples were dominated by lactobacilli, while the remaining samples had low numbers of lactobacilli but significantly higher numbers of Prevotella species. The different primer pairs produced broadly similar data but proportions of the phylum Bacteroidetes were significantly higher when primer 1387R was used. All of the primer sets underestimated the proportion of Actinobacteria compared to culture. Pyrosequencing analysis of the samples was performed to a depth of sequencing of 4293 sequences per sample which were identified to 264 species-level taxa, and resulted in significantly higher coverage estimates than the clonal analysis. Pyrosequencing, however, also underestimated the relative abundance of Actinobacteria compared to culture.